Analisis Formalisme Meaningful Participation Dalam Pembentukan Undang-Undang Di Indonesia - Abdur Rahim; Ahmad Zaelani; Fatur Rahman Al Mugni; Edi Mulyadi; Sumariyadi; Abdul Hamid (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
Indonesia is a country that places popular sovereignty as the highest foundation of state governance, including public involvement in every legislative process. This study aims to analyze the phenomenon of formalism in the implementation of meaningful public participation following Constitutional Court Decision No. 91/PUU-XVIII/2020. Although legal norms have guaranteed the right to be heard, the right to be considered, and the right to be explained, the reality of legislation reveals a tendency toward participation that is merely procedural or administrative in nature. Using a normative legal research method through a legislative analysis and case study approach, this study examines the drafting processes of the Job Creation Law, the IKN Law, and the RKUHAP. The findings reveal that meaningful participation is often reduced to merely fulfilling formal requirements to avoid annulment by the Constitutional Court, while the substance of public aspirations is overlooked in the fast-paced and closed legislative process. This contradiction has led to a crisis of democratic legitimacy and a decline in the quality of the resulting legal products. This study recommends that the Constitutional Court strengthen its formal review standards to ensure that public participation is conducted in a fair and transparent manner and has a tangible impact on the substance of legislation.